From Bonsai to big Banyan: Scaling up Community Driven Green Livelihood Initiatives - Kumar, Sachin; Marh, Bhupinder S. (National Geographical Journal of India, 2022)
Livelihood promotion has assumed unprecedented primacy in the contemporary developmental discourse primarily because three core developmental challenges, namely economic poverty, social inequality and environmental nonsustainability appear to be inextricably linked with livelihoods. At the same time, the world is witnessing multiple stressors at global, regional and local levels interacting and reinforcing each other to affect livelihood opportunities. It is also important to highlight that all types of livelihood interventions may not be sensitive to environment. In fact, insensitive livelihood policies and practices have been found as one of the core reasons behind growing environmental degradation. In this context, the call for sustainable development makes it imperative to design and promote green livelihood projects. Against this backdrop, this paper assertively proposes that it is imperative to scale up community driven green livelihood initiatives (CDGLIs) in order to ensure just, inclusive and sustainable development for the teeming millions of the country. After summarizing the concepts related to promotion of CDGLIs and scaling up, the paper articulates key rationale for the same. Finally, it ends with listing out key considerations for successful scaling up of CDGLIs.